Smart sports immersive martial arts teaching mode analysis - Zhou, Guilin; Xie, Zhenyu (LPPM STIKI Malang, 2024)
This paper aims to deeply explore the immersive martial arts teaching mode under the background of intelligent sports. By analyzing the connotation and characteristics of the immersive martial arts teaching mode, its construction elements under the support of intelligent sports technology, including the application of virtual reality (VR), augmented reality (AR), intelligent equipment and other scientific and technological equipment in teaching. Study the influence of this mode on students' learning effect, interest cultivation and wushu inheritance, and put forward corresponding countermeasures for the possible problems in the implementation process, so as to explore a new teaching mode for the innovation and development of martial arts teaching in the new era.